MODEL PENYAJIAN QIRAAT DALAM TAFSIR AL-MISBAH - Syarifah Laili (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
The Tafsir Al-Misbah is a high-value tafsir that was born of the Indonesian Tafsir figure, M. Quraish Shihab. This work is said to be a relatively complete tafsira and tries to prioritize the value of relevance of the Quran with life in accordance with its times. This paper aims to describe the model of presenting the Qur'an chosen by M.Quraish Shihab in Tafsir Al-Misbah by applying qualitative research methods that are considered to have relevance in the study of the Quran and tafsir. Using appropriate library data sources and subsequently analyzed with content anlysist approach. This study found that there are at least three models of presentation of the Qur'an in the Tafsir Al-Misbah, namely without or by mentioning the Quran and comparing the difference between one Quran and another according to the needs of interpretation